A regional comparative study of Middle group and lower group chromitites in the critical zone of the Bushveld Complex - Hasch, Maximilian (My University, 2022)
The present study focuses on Lower Group (LG1-7) and Middle Group (MG0-4) chromitites in the Critical Zone of the Bushveld Complex and aims at gaining new insight into their genesis. Field observations have been made in open pit and underground mines at a multitude of locations in the Eastern and Western Lobes of the Bushveld Complex. These allow for a description of the morphology and field relations of chromitites on a regional scale and for a regional perspective on their formation. Furthermore, a vertical chemical profile was drawn through the LG6 chromitite in a drill core from the Eastern Lobe, which is used to back some of the claims made from field observations. Chromitites exhibit distinct morphologies at different locations, as they appear as one, two or three chromitite layers and vary in thickness. It is inferred that this represents a regional structure of bifurcating chromitites. Owing to the significant size of this structure, bifurcations are seldom observed in outcrop. The LG6 chromitite contains up to five sublayers. Chemical data suggest that these sublayers are of magmatic origin and it is inferred that they formed in a similar fashion to the multiple chromitite layers of the MG chromitite packages. Evidence for magmatic erosion of footwall rocks to chromitites was documented in the form of chromitites transgressing their footwall and the presence of large erosional footwall remnants in chromitite layers. Furthermore, two potholes, roughly circular depressions, have been observed. The potholes contain chromitite layers and transgress their footwall rocks, suggesting that chromite deposition was preceded by magmatic erosion. The lateral thickness differences in silicate layers suggest that this erosion was regionally heterogeneous. Depending on the rate of erosion, it may have removed part of the footwall, the entire footwall or even part of the underlying chromitite. Upon cooling, the magma deposited a chromitite layer. The relations between chromitites and their host rocks suggest that the chromitites crystallised on the erosion surface. Depending on the degree of magmatic erosion, a few separate chromitite layers or a single chromitite layer would form from several influxes of fresh magma into the chamber.
A thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, University of the Witwatersrand, 2022
Keywords: Middle Group chromitites; Lower Group chromitites; Bushveld Complex